2020
DOI: 10.1002/lipd.12216
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Influence of Saturated Fatty Acids on Malignant and Nonmalignant Human Lung Epithelial Cells

Abstract: The impact of saturated fatty acids (FA) on viability and properties of malignant and nonmalignant cells has not been studied in detail so far. The present study was aimed at evaluation of the influence of saturated FA (10:0–18:0) on malignant (A459) and nonmalignant (BEAS‐2B) human lung epithelial cells. FA strongly affected A549 cells, but not BEAS‐2B cells. Viability of A549 cells incubated with 14:0–18:0 was decreased by 53–91% as compared to untreated cells. Cell membrane stiffness in those cells as measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…BEAS-2B cells, on the other hand, constitute a cell line with larger morphology and are well spread compared to A549 cells. Reczyńska et al 52 examined the stiffness values of these two cell lines with AFM and similarly reported that A549 cells were stiffer than BEAS-2B cells. As stated in various sources, cell stiffness is closely associated with actin stress fibers in the cell cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…BEAS-2B cells, on the other hand, constitute a cell line with larger morphology and are well spread compared to A549 cells. Reczyńska et al 52 examined the stiffness values of these two cell lines with AFM and similarly reported that A549 cells were stiffer than BEAS-2B cells. As stated in various sources, cell stiffness is closely associated with actin stress fibers in the cell cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…No such effect has been observed for microparticles formed from a mixture of myristic and palmitic acids. In other studies, it has been observed that saturated fatty acids alone can reduce malignant cells (A540 line) viability with no effect on nonmalignant cells (BEAS-2B line) . Therefore, there are experimental evidences that both PAX and saturated fatty acids affect malignant cells, whereas SPIONs do not affect microparticles efficacy, properties, or topology.…”
Section: Introductionmentioning
confidence: 94%
“…In other studies, it has been observed that saturated fatty acids alone can reduce malignant cells (A540 line) viability with no effect on nonmalignant cells (BEAS-2B line). 17 Therefore, there are experimental evidences that both PAX and saturated fatty acids affect malignant cells, whereas SPIONs do not affect microparticles efficacy, properties, or topology. As stated above, when microparticles are inhaled, they first encounter the mucus layer.…”
Section: Introductionmentioning
confidence: 99%
“…120 Reczyn ´ska et al suggested that a large intake of NSFAs by cancerous A549 cells led to decreased stiffness of cell membranes and reduced cell viability, whereas the cell viability of non-malignant BEAS-2B cells was barely affected. 121 Such a discrepancy indicates that the delivery of excessive NSFAs to cancer cells may provide an alternative way for targeted cancer therapy.…”
Section: Cancer Therapymentioning
confidence: 99%